2020
DOI: 10.1038/s41597-019-0340-y
|View full text |Cite|
|
Sign up to set email alerts
|

The GenTree Dendroecological Collection, tree-ring and wood density data from seven tree species across Europe

Abstract: The dataset presented here was collected by the GenTree project (EU-Horizon 2020), which aims to improve the use of forest genetic resources across Europe by better understanding how trees adapt to their local environment. This dataset of individual tree-core characteristics including ring-width series and whole-core wood density was collected for seven ecologically and economically important European tree species: silver birch (Betula pendula), European beech (Fagus sylvatica), Norway spruce (Picea abies), Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
291
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(298 citation statements)
references
References 26 publications
1
291
0
Order By: Relevance
“…The delineation performance shows errors of ms, ms and ms in the onset and of ms, ms and ms in the offset for delineation, with Dice scores of 88.99%, 92.05%, 88.40% for the P, QRS and T waves, respectively. This model was used to predict some registries in 19 , shown in Supplementary Figs. S1 – S10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delineation performance shows errors of ms, ms and ms in the onset and of ms, ms and ms in the offset for delineation, with Dice scores of 88.99%, 92.05%, 88.40% for the P, QRS and T waves, respectively. This model was used to predict some registries in 19 , shown in Supplementary Figs. S1 – S10 .…”
Section: Resultsmentioning
confidence: 99%
“…A second dataset containing outflow tract ventricular arrhythmias in the 12-lead ECG 19 was employed to qualitatively assess the fitness of the trained models, with some results reported in the Supplementary Figs. S1 – S10 .…”
Section: Methodsmentioning
confidence: 99%
“…These values indicated that Alphasense is not suitable for such low-concentration monitoring, while the MEE reference instrument is qualified. The low SO 2 concentrations are largely attributed to the strong implementation of the SO 2 control policy; thus, good monitoring and treatment measures were achieved at the stacks near large individual emissions factories [ 49 ], and coal consumption was largely reduced due to the shift to natural gas [ 50 ]; these measures reduced the SO 2 emissions by 62% from 2010–2017 [ 51 ]. Due to the low SO 2 environmental concentrations and subsequent poor performance of the sensor response, we mainly analyze CO, O 3 , and NO 2 in the following text.…”
Section: Resultsmentioning
confidence: 99%
“…In the research of Spinelle [ 48 ], an Alphasense-O 3 B4 sensor was used, and its effect after MLR correction reached approximately R 2 = 0.5. There are few existing studies on correcting the low-cost sensor of O 3 using deep learning and other algorithms, and the control of O 3 pollution has attracted increasing attention from the public and scientific community [ 49 ], so the correction and application of a low-cost sensor for O 3 is urgently needed. For O 3 sensor calibration in our study ( Figure 4 b), the corrected results of the training set and test set are R 2 = 0.75 (R 2 = 0.54 before correction) and R 2 = 0.77 (R 2 = 0.59 before correction), and the LSTM correction effect of O 3 is significantly improved compared with RFR, especially in the test set.…”
Section: Resultsmentioning
confidence: 99%
“…Xu group organized them and introduced descriptors for predicting ITR by machine learning method 8 , 9 . Details of the developed descriptors and collected ITR were explained in the previous work 41 . And data could be found in the file named “training dataset for ITR prediction.xlsx” and downloaded directly from https://doi.org/10.5281/zenodo.3564173 .…”
Section: Methodsmentioning
confidence: 99%